2017
DOI: 10.1002/aic.15922
|View full text |Cite
|
Sign up to set email alerts
|

Plasma assisted nitrogen oxide production from air: Using pulsed powered gliding arc reactor for a containerized plant

Abstract: The production of NO x from air and air 1 O 2 is investigated in a pulsed powered milli-scale gliding arc (GA) reactor, aiming at a containerized process for fertilizer production. Influence of feed mixture, flow rate, temperature, and Ar and O 2 content are investigated at varying specific energy input. The findings are correlated with high-speed imaging of the GA dynamics. An O 2 content of 40-48% was optimum, with an enhancement of 11% in NO x production. Addition of Ar and preheating of the feed resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 46 publications
2
74
0
Order By: Relevance
“…An example of noise experienced in Q-V diagrams is shown in Figure 10, as well as Refs. [47,48]. The unfiltered plot in Figure 10 shows background noise during the capacitive phase, but larger spikes during the discharging phase of the DBD cycle.…”
Section: Noisy Q-v Diagramsmentioning
confidence: 98%
“…An example of noise experienced in Q-V diagrams is shown in Figure 10, as well as Refs. [47,48]. The unfiltered plot in Figure 10 shows background noise during the capacitive phase, but larger spikes during the discharging phase of the DBD cycle.…”
Section: Noisy Q-v Diagramsmentioning
confidence: 98%
“…Research carried out by Patil et al shown a significant role of O 2 admixtures in the formation of NO x . For pulsed power supply, air mixtures were not only economically advantageous, but also allowed to obtain a lot of NO 2 that increased with increasing O 2 fraction [29]. Experiment on the sinusoidal and pulsed power supply for water spray GA carried out by Burlica and Locke has shown significant concentration of nitrates NO 3 − formed in water, when the working gases were air and N 2 , compared to very low levels obtained for Ar and O 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Besides this classical configuration, there are several other designs, addressing the need of specific optimization for specific applications, like for example discharges with multiple electrodes [3,4], a magnetically stabilized gliding arc (MGA) reactor [5], a reactor with vortex gas flow [6,7], etc. The GAD is very promising for various applications, such as CO 2 conversion [7,8], dry reforming of methane [9,10], N 2 fixation [11,12], surface treatment [13] and even waste treatment [14]. This type of discharge is attractive, because it allows the generation of relatively dense plasma in the order 10 20 -10 22 m -3 while sustaining a relatively low gas temperature below 2000-3000 K. Taking into account that the electron temperature in these discharges is in the order of 1-2 eV, it is clear that GADs produce thermally non-equilibrium plasmas, which are found to be preferable for various plasma assisted gas conversion processes [1].…”
Section: Introductionmentioning
confidence: 99%